Clima y satisfacción laboral como determinantes del desempeño de la empresa ENVATUB S.A. - Comina Fonseca, Andrea Estefanía (2018)
main objective of this research project was to verify that climate and job satisfaction are determinants of the performance of workers of the company ENVATUB SA, considering that currently being strengthened internally helps, to actively participate in the economic, business and market dynamics to be able to survive, in addition to having the ability to promote learning that strengthens the strategies implemented and the experiences generated to obtain greater experience in this regard, identifying weaknesses and strengths that exist in factors such as: structure, standards, responsibility, conflict, risk , reward, interpersonal relations, identity, in regard to work environment, at the same time the factors of job satisfaction were investigated, such as working conditions, benefits, social or personal recognition and significance of the task, which are an important part to generate good d work career. Therefore, it was necessary to carry out the fieldwork, with a mixed approach that allowed for the numerical measurement and compilation of demographic data. Through the type of descriptive research, the current situation of the organization was described, and through the type of correlational investigation allowed perform the correlation between the study variables, the state of work climate was evaluated through the "Measurement Instrument of Litwin and Stringer", for the measurement of job satisfaction the "Scale of Opinions SL-SPC" was used, elaborated by Sonia Palma (2005), and for the measurement of work performance, the "Rocca Adriana Questionnaire" was used. The results obtained from the diagnosis were analyzed through a statistical application in the SPSS, verifying the relationship between the dependent variable (work performance) and the independent variable (work climate) where the "r" of Pearson throws 0.942, and between Labor satisfaction (Independent Variable) and labor performance (dependent variable) yields 0.813, resulting in that, between the climate, and job performance if there is a direct relationship. The results obtained through the analysis allowed to identify that in the company Envatub sa, the negative factors in the work climate are: cooperation, challenge, standards, identity, reward, in job satisfaction are: recognition and significance of the task while in The variable work performance are: Quality of work and Ability to plan.